(untitled) (Research, Society and Development, 2022)
The main objective of this study is to review the literature regarding the etiology of erythroblastosis fetalis, emphasizing its physiology. Citing the ways of diagnosing the disease, variations in therapeutic practices over the years and their impact on prognosis. This is an integrative literature review. the following databases were consulted: Medical Publications (PubMed), Scopus (Elsevier), Google Scholar and Scientific Electronic Library Online (SciELO). The following terms were used in the databases: Erythroblastosis fetalis, ABO System, Rh System, Diagnosis and Treatment. Within the time frame from 2017 to 2022. The 19 selected studies addressed are widely discussed, in various aspects, such as the importance of diagnosing DHPN, as well as its prevention. Furthermore, among the selected articles, it is noted that the search for an effective therapy is constant in patients affected by DHPN, showing new discoveries and increasing the available possibilities. From this, it is important to emphasize that new health policies must be implemented in order to minimize the cases of the pathology, such as updating and training courses for all professionals who are directly linked to obstetrics, as well as accessible lectures for the population of old age. fertile in general, prioritizing couples who are expecting their second child.